Non-financial assets impairments in light of IAS/IFRS case of SAIDAL GROUP - OUARAB , ALI (Journal of Research in Finance and Accounting, 2021)
This article aims to address the main aspects related to impairments of non-financial assets with reference to IAS 36, particularly with regard to the impairment tests and their implementation, highlighting the disposition of financial accounting system regarding this item, and analyzing the differences between these two standards in this topic. The study found that the tests of depreciation of non-financial assets are complicated, because of their association with various economic and accounting factors, as the discounted rate, determining the value in use, and cash-generating unit, whose value is difficult to test. It has also been concluded, after the analysis that the financial accounting system is very close to IAS 36, with regard to logic and philosophy, while far from it in explanations and clarifications.